A Modified Giffler and Thompson Genetic Algorithm on the Job Shop Scheduling Problem (MATEMATIKA, 2006)
Job Shop Scheduling Problem (JSSP) is one of the well-known hardest combinatorial optimization problems. The goal of this research is to study an efficient scheduling method based on Genetic Algorithm (GA) to address JSSP. A GA based on Giffler and Thompson (GT) algorithm known as GT-GA that utilizes the GT crossover is investigated. This algorithm is modified to produce better results than the existing algorithm by using Visual Prolog programming language. Keywords: Job Shop Scheduling Problem; Genetic Algorithms; GT-GA.